The Corporate Social Responsibility Information Environment: Examining the Value of Financial Analysts’ Recommendations - Lee, Changhee; Palmon, Dan 1941-; Yezegel, Ari (2018)
This study examines the relationship between corporate social responsibility (CSR)-related information and the value of financial analysts’ stock recommendations. The information environment in which analysts operate in is affected by CSR-related reports that companies voluntarily issue as well as information that becomes available through third-party analysis and rating institutions. We find an inverse relationship between the value of both upgrade and downgrade revisions and the supply of CSR-related information compiled by third-party institutions, suggesting that CSR-related data are associated with a richer information environment that makes it more challenging for analysts to issue informative recommendations, thereby mitigating their contribution to the price discovery process. We further find that the value of analysts’ recommendation revisions is lower for companies that voluntarily issue CSR-related reports compared to those that do not make such disclosures and that the overall effect of CSR on the informativeness of analysts is stronger in the recent years. Our findings have implications for the evolution of CSR reporting as the incorporation of CSR-related information into market prices legitimizes the relevance of such reports. Furthermore, these findings contribute to our understanding of the role and value of information intermediaries in changing information environments.
Keywords: Market efficiency; Stock recommendations; Disclosure; Financial analysts; Corporate Social Responsibility